A hepatocellular carcinoma model with and without parenchymal liver damage that integrates technical and pathophysiological advantages for therapy testing - Karina Benderski; Paul Schneider; Panayiotis Kordeves; Michael Fichter; Jenny Schunke; Federica De Lorenzi; Feyza Durak; Barbara Schrörs; Özlem Akilli; Fabian Kiessling; Matthias Bros; Mustafa Diken; et al. (Pharmacological Research)
Hepatocellular Carcinoma (HCC) is the most common form of primary liver cancer, with cirrhosis being its strongest risk factor. Interestingly, an increasing number of HCC cases is also observed without cirrhosis. We developed an HCC model via intrasplenic injection of highly tumorigenic HCC cells, which, due to cellular tropism, invade the liver and allow for a controllable disease progression. Specifically, C57BL/6JRj mice were intrasplenically inoculated with Dt81Hepa1–6 HCC cells, with a subgroup pre-treated with CCl4 to induce cirrhosis (C-HCC). At four weeks post-inoculation, mice were sacrificed, and diseased livers were analyzed via histology, flow cytometry, and RT-qPCR to profile the extracellular matrix (ECM), angiogenesis, and immune cells. In addition, tumor-bearing mice were treated with the first-line therapy, AtezoBev, to assess therapeutic responsiveness of the model. Dt81Hepa1–6 cells displayed similar gene expression as human HCC. After intrasplenic injection, all mice developed multifocal disease. C-HCC mice had a significantly higher tumor load than non-cirrhotic HCC mice. Both HCC and C-HCC models displayed extensive ECM formation, increased levels of vascularization, and immune cell infiltration compared to healthy and non-cancerous cirrhotic livers. AtezoBev treatment produced robust antitumor efficacy, validating the model’s suitability for therapy testing. In conclusion, we established a rapidly developing and high-yield HCC model through a simple intrasplenic injection, with or without cirrhotic damage. The model overexpressed key human HCC genes and showed high responsiveness to first-line treatment. Our model uniquely combines all the above-mentioned features, promoting its use towards HCC therapy testing.